Half a Century of Hawaiian Marine Natural Products - Hagiwara, Kehau A.; Wright, Anthony D. (Planta Medica, 2016)
The following review covers the primary literature concerning marine natural products isolated for the first time from organisms collected around the islands of Hawaii published in the 51-year period 1964 to July 2015. The review is divided into seven main sections based on major taxonomic groupings; algae, sponges, mollusks, miscellaneous invertebrates, cyanobacteria, bacteria, and fungi. The aim of the review is to discuss the compounds and information concerning their original biological activity and other potentially interesting properties. The majority of the 320 structures of isolated compounds are not shown directly in the review but are contained in the Supporting Information section in 22 figures, Figs. 1 S–22 S. The Supporting Information section also contains Table 1 S that has information relating to the taxonomic identification of the source organism of each compound, collection location of the source organism, a trivial or semi-systematic name for each compound, as well as its general structural class. The authors hope that this review will be the spawning ground for other reviews and the basis for a great deal more research into the marine life found in Hawaiian waters.
Keywords: Hawaii; marine; natural products; algae; sponges; cyanobacteria; bacteria; fungi